Skeletal Muscles Do Not Undergo Apoptosis During Either Atrophy or Programmed Cell Death-Revisiting the Myonuclear Domain Hypothesis - Schwartz, Lawrence M. (Frontiers in Physiology, 2019)
Skeletal muscles are the largest cells in the body and one of the few syncytial ones. There is a longstanding belief that a given nucleus controls a defined volume of cytoplasm, so when a muscle grows (hypertrophy) or shrinks (atrophy), the number of myonuclei change accordingly. This phenomenon is known as the “myonuclear domain hypothesis”. There is general agreement that hypertrophy is accompanied by the addition of new nuclei from stem cells to help the muscle meet the enhanced synthetic demands of a larger cell. However, there is considerable controversy regarding the fate of pre-existing nuclei during atrophy. Many researchers have reported that atrophy is accompanied by the dramatic loss of myonuclei via apoptosis. However, since there are many different non-muscle cell populations that reside within the tissue, these experiments cannot easily distinguish true myonuclei from those of neighboring mononuclear cells. Recently, two independent models, one from rodents and the other from insects, have demonstrated that nuclei are not lost from skeletal muscle fibers when they undergo either atrophy or programmed cell death. These and other data argue against the myonuclear domain hypothesis and suggest that once a nucleus has been acquired by a muscle fiber it persists.